ASD Is Not DLI: Individuals With Autism and Individuals With Syntactic DLI Show Similar Performance Level in Syntactic Tasks, but Different Error Patterns - Sukenik, Nufar; Friedmann, Naama (Frontiers in Psychology, 2018)
Do individuals with autism have a developmental syntactic impairment, DLI(formerly known as SLI)? In this study we directly compared the performance of 18 individuals with Autism-Spectrum-Disorder(ASD) aged 9-18 years with that of 93 individuals with Syntactic-Developmental-Language-Impairment(SyDLI) aged 8;8-14;6(and with 166 typically-developing-children aged 5;2-18;1). We tested them in three syntactic tests that assess the comprehension and production of syntactic structures that are known to be sensitive to syntactic impairment: elicitation of subject and object relative clauses, reading and paraphrasing of object relatives, and repetition of complex syntactic structures including Wh-questions, relative-clauses, topicalized sentences, sentences with verb movement, sentences with A-movement, and embedded sentences. The results were consistent across the three tasks: prima facie, the overall rate of correct performance on the syntactic tasks is similar for ASD and SyDLI. However, once we look closer, they are very different. The types of errors that the ASD children make differ from those of the SyDLI group–the ASD children provide various types of pragmatically infelicitous responses that are not evinced in the SyDLI or TD groups. The two groups also differ in the pattern of performance – the children with SyDLI show a syntactically-principled pattern of impairment, with selective difficulty in specific sentence types(such as sentences derived by movement of the object across the subject), and normal performance on other structures(such as simple sentences). In contrast,the ASD-participants showed generalized low performance on the various sentence structures. Syntactic performance was far from consistent within the ASD-group. Whereas all ASD-participants had errors that can originate in pragmatic/discourse difficulties, seven of them had completely normal syntax in the structures tested, and were able to produce,understand,and repeat relative-clauses,Wh-questions,and topicalized sentences. Only one ASD participant showed performance with syntactically-principled deficit similar to that of individuals with syDLI. We conclude that not all individuals with ASD have syntactic difficulties, and that even when they fail in a syntactic task, this does not necessarily originate in a impairment.This shows that looking only at the total score in a syntactic test may be insufficient, and a fuller picture emerges once the performance on different structures and error types are analyzed.